History of the Erbil Plain (Dizaiy Tribe as an example), Roots and Traditions - Eman TahseenYaseen; Snur Sabah Sediq (Zanco Journal of Human Sciences, 2026)
The Dizaiy tribe has a long and distinguished history in the Erbil Plain. Although opinions vary regarding the exact time of their arrival in the region, there is a general consensus that their presence dates back to ancient times. Initially, their population was small, but over time, they grew in number and accumulated significant property and influence. This growth positioned them as key decision-makers, including in political affairs. Culturally, the Dizaiy tribe shared similarities with the local inhabitants in customs and dress due to their active social engagement. Nevertheless, they preserved their distinct identity, maintaining a strong sense of internal cohesion. Marriage was traditionally confined within the tribe, as they preferred not to intermarry with outsiders—a practice that strengthened their unity. At the same time, the Dizaiy were known for their resilience and courage, often standing firmly against oppression and refusing to submit to unjust authority.